Hydrogeological settings of a volcanic island (San Cristóbal, Galapagos) from joint interpretation of airborne electromagnetics and geomorphological observations - Pryet, A.; d'Ozouville, N.; Violette, S.; Deffontaines, B.; Auken, E. (Hydrology and earth system sciences, 2012)
Many volcanic islands face freshwater stress and the situation may worsen with climate change and sea level rise. In this context, an optimum management of freshwater resources becomes crucial, but is often impeded by the lack of data. With the aim of investigating the hydrogeological settings of southern San Cristóbal Island (Galapagos), we conducted a helicopter-borne, transient electromagnetic survey with the SkyTEM system. It provided unprecedented insights into the 3-D resistivity structure of this extinct basaltic shield. Combined with remote sensing and fieldwork, it allowed the definition of the first hydrogeological conceptual model of the island. Springs are fed by a series of perched aquifers overlying a regional basal aquifer subject to seawater intrusion. Dykes, evidenced by alignments of eruptive cones at the surface, correspond to sharp sub-vertical contrasts in resistivity in the subsurface, and impound groundwater in a summit channel. Combined with geomorphological observations, airborne electromagnetics are shown to be a useful for hydrogeological exploratory studies in complex, poorly known environments. They allow optimal development of land-based geophysical surveys and drilling campaigns.